Is Sub-Epithelial Connective Tissue Graft Really a Gold Standard for the Treatment of Gingival Recession Defects? - Ajay Mahajan; Ashu Bhardwaj; Poonam Mahajan (Wolters Kluwer Medknow Publications, 2011)
Gingival recession defects are one of the most common peri-odontal problems. In the past few decades there have been several attempts to treat the gingival recession defects. Among all the treatment options the sub-epithelial connective tis-sue graft is still the most widely used. The sub-epithelial connective tissue graft is considered to produce high percentage of root coverage and therefore considered to be the gold standard technique for the treatment of gingival reces-sion defects. Despite many research papers favoring the use of sub-epithelial connective tissue graft, recent data suggests no major difference in terms of percent root coverage when various other techniques for the treatment of gingival recession defects are compared with each other. In the light of present clinical evidence the criteria to determine whether sub-epithelial connective tissue graft technique should be considered a gold standard or not for be treatment of gingival recession must be re-evaluated. This article highlights some inherent drawbacks associated with sub-epithelial connective tissue graft and emphasizes the need to consider other available techniques for the treatment of gingival recession defects.